2014
DOI: 10.1038/ncomms6271
|View full text |Cite
|
Sign up to set email alerts
|

Translocation path of a substrate protein through its Omp85 transporter

Abstract: TpsB proteins are Omp85 superfamily members that mediate protein translocation across the outer membrane of Gram-negative bacteria. Omp85 transporters are composed of N-terminal POTRA domains and a C-terminal transmembrane b-barrel. In this work, we track the in vivo secretion path of the Bordetella pertussis filamentous haemagglutinin (FHA), the substrate of the model TpsB transporter FhaC, using site-specific crosslinking. The conserved secretion domain of FHA interacts with the POTRA domains, specific extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 45 publications
4
53
0
Order By: Relevance
“…The new structure of FhaC (PDB code 4QKY) now shows loop 6 in the same conformation as observed for BamA and TamA, with the conserved (V/I)RG(F/Y) motif interacting with the opposite wall of the β-barrel domain (Figure 3C). These new structural insights align well with recent biophysical and crosslinking studies for FhaC and BamA which have both shown that a conformational change in loop 6 is not required for function [26,32,33]. While the new FhaC structure helps solidify the idea that loop 6 and the (V/I)RG(F/Y) do not cycle between two differing conformations as first thought, exactly what role this highly conserved motif serves remains elusive.…”
Section: A Shared Conformation For Loop 6 Among the Omp85 Superfamilysupporting
confidence: 72%
See 1 more Smart Citation
“…The new structure of FhaC (PDB code 4QKY) now shows loop 6 in the same conformation as observed for BamA and TamA, with the conserved (V/I)RG(F/Y) motif interacting with the opposite wall of the β-barrel domain (Figure 3C). These new structural insights align well with recent biophysical and crosslinking studies for FhaC and BamA which have both shown that a conformational change in loop 6 is not required for function [26,32,33]. While the new FhaC structure helps solidify the idea that loop 6 and the (V/I)RG(F/Y) do not cycle between two differing conformations as first thought, exactly what role this highly conserved motif serves remains elusive.…”
Section: A Shared Conformation For Loop 6 Among the Omp85 Superfamilysupporting
confidence: 72%
“…In addition, the other extracellular loops in FhaC have an open conformation; the structure of FhaC is well suited to mediate secretion given the less restricted passage through the β-barrel domain to the surface once the H1 helix in the pore has been ejected. (Figure 3A) [30,32,33]. However, BamA and TamA both differ significantly in that loop 6 is able to fully cap their β-barrel domain, sealing the membrane and occluding a direct path from the periplasm to the outside of the cell (Figures 2A and 3A) [22,25].…”
Section: Lateral Opening In Bamamentioning
confidence: 99%
“…In addition, we found that the pore-forming domain also influences this specificity. In particular, the chimeric protein containing the periplasmic domain of HMW1B and the pore-forming domain of EtpB was associated with only low-level secretion of the HMW1 propiece and only low-level HMW1-mediated adherence, emphasizing that not all TpsB pore-forming domains are the same, consistent with recent observations by Baud et al (41).…”
supporting
confidence: 80%
“…As indicated by its name, TPS systems are characterized by two proteins, generically known as TpsB (CdiB) and TpsA (CdiA), that are secreted across the Gram-negative envelope. TpsB partners are outer-membrane proteins of the Omp85 family, and export TpsA exoprotein cargos through the central lumen of their β-barrels 21 . In many instances, the TpsA partner is thought to remain tethered non-covalently to TpsB, thereby projecting the exoprotein outward from the surface of the secreting bacterium (Fig.…”
Section: The Discovery Of Contact-dependent Growth Inhibition (Cdi)mentioning
confidence: 99%
“…The N-terminal region also contains the TPS transport domain (also known as the hemagglutinin activation domain, PF05860), which is required for export across the outer membrane. CdiB recognizes the TPS transport domain as it emerges into the periplasm and transports CdiA through the central pore in its β-barrel domain 21; 32; 33 . CdiA proteins also share FHA-1 (PF05594) and FHA-2 (PF13332) peptide repeats with FHA/FhaB (Fig.…”
Section: Architecture Of Cdia Effector Proteinsmentioning
confidence: 99%